Rheological and Quality Characteristics of Taftoon Bread as Affected by Salep and Persian Gums - M. A. Sahari; R. Mohammadi; Z. Hamidi Esfehani (International Journal of Food Science)
Effects of salep gum at concentrations of 0.5%, 1%, 3%, and 5% (w/w flour basis) and the Persian gum at concentrations of 0.5%, 1%, and 3% (w/w flour basis) and combination of the two gums at concentrations of 0.5% + 0.5%, 0.75% + 0.25%, and 0.25% + 0.75% on rheological properties of the wheat flour dough and quality of Taftoon bread were studied with regard to retardation of staling. Rheological (farinograph and extensograph) characteristics, staling, and organoleptic evaluations were performed on the dough and the resulting Taftoon bread. Statistical results showed that the salep gum at 5% and Persian gum at 3% (w/w flour basis) had a significant effect on the dough properties. Salep and Persian gums when each separately added increased and decreased dough water absorption, respectively. Both hydrocolloids increased the dough resistance to extension and decreased its extensibility. Persian gum shows dual nature in water absorption and some other baking properties. Textural studies revealed that addition of 5% salep gum (w/w flour basis) reduced the bread crumb firmness and delayed the staling process of the Taftoon bread. X-ray diffraction study also confirmed this result.